The Experimental Experience of Motion Kinematics in Biology Class Using PhET Virtual Simulation and Its Impact on Learning Outcomes - Ni Nyoman Sri Putu Verawati; Lia Saptini Handriani; Binar Kurnia Prahani (International Journal of Essential Competencies in Education, 2022)
This study aimed to provide biology students with a motion kinematics experimental experience using virtual PhET simulations and explore the improvement of their physics learning outcomes. Pre-experimental (pretest-posttest experimental design) was conducted in this study, pretest-posttest was carried out before and after the learning treatment, while the learning treatment was motion kinematics experiment using virtual PhET simulation. The research sample was taken purposively, they were 24 students of the Biology Education Study Program, FKIP Mataram University who took Basic Physics courses. Student learning outcomes were measured using a test instrument. Learning outcomes data were analyzed descriptively with the average score of achievement or performance of students' cognitive learning outcomes on pretest and posttest, as well as n-gain analysis. In addition, statistical analysis (Wilcoxon test) was used to determine the difference in the average score of student learning outcomes between pre-posttest (p < 0.05). The results of the descriptive analysis showed that the average score of student learning outcomes increased from pretest to posttest with successive criteria from "less" to "good," an increase in student learning outcomes with high criteria with an n-gain score of 0.71. The results of the statistical test showed that there was a significant difference in the average score of student learning outcomes before and after the motion kinematics experiment using PhET virtual simulation. The results in this study provide a learning experience related to ways of conducting physics concepts that are more meaningful in the learning process that can be widely used in routine physics teaching in the classroom.